SISTEM KEBIJAKAN OBJEK VITAL NASIONAL, PENGAMANAN FILE DAN PENGAMANAN CYBER TERHADAP BANK MANDIRI - Edy Soesanto; Husni Fauzi Ramadhan; Ivan Ardiansyah; Rizky Maulana (Cross-border, 2023)
The insight from the management of security to the company's intuition is significant. In the banking industry, security management such as vital object policies, file security and cyber security have an important role in maintaining and keeping confidential the data of customers in the company. In preventing the leakage of customer data, companies must pay more attention to objects that are too crucial. It is not easy to give company access to employees outside the company.